Effects of FSH on the expression of receptors for oocyte-secreted factors and members of the EGF-like family during in vitro maturation in cattle - Caixeta, Ester Siqueira [UNESP]; Machado, Mariana Fernandes [UNESP]; Ripamonte, Paula [UNESP]; Price, Christopher; Buratini, José [UNESP] (My University, 2013)
FSH induces expansion of bovine cumulus-oocyte complexes (COCs) in cattle, which can be enhanced by oocyte-secreted factors (OSFs). In this study it was hypothesised that FSH stimulates COC expansion in part from direct stimulation of the epidermal growth factor (EGF)-like ligands amphiregulin (AREG), epiregulin (EREG) and betacellulin (BTC), but also in part through regulation of OSFs or their receptors in cumulus cells. Bovine COCs were cultured in defined medium with graded doses of FSH. In the absence of FSH, COCs did not expand. FSH caused cumulus expansion, and increased the abundance of AREG and EREG mRNA in a time- and dose-dependent manner, but decreased BTC mRNA levels. FSH had modest stimulatory effects on the levels of mRNA encoding the bone morphogenetic protein 15 (BMP15) receptor, BMPR1B, in cumulus cells, but did not alter mRNA expression of the growth and differentiation factor 9 (GDF9) receptor, TGFBR1. More interestingly, FSH dramatically stimulated levels of mRNA encoding two receptors for fibroblast growth factors (FGF), FGFR2C and FGFR3C, in cumulus cells. FSH also stimulated mRNA expression of FGFR1B, but not of FGFR2B in cumulus cells. Based on dose-response studies, FGFR3C was the receptor most sensitive to the influence of FSH. This study demonstrates that FSH stimulates the expression of EGF-like factors in bovine cumulus cells, and provides evidence that FSH differently regulates the expression of distinct receptors for OSFs in cumulus cells. © CSIRO 2013.
Keywords: cumulus expansion; EGF-like ligands; amphiregulin; betacellulin; bone morphogenetic protein 15 receptor; bone morphogenetic protein receptor 1B; epiregulin; fibroblast growth factor receptor; fibroblast growth factor receptor 1B; fibroblast growth factor receptor 2c; fibroblast growth factor receptor 3c; follitropin; growth differentiation factor 9; messenger RNA; unclassified drug; animal cell; cell culture; cell expansion; cell maturation; cell stimulation; controlled study; cumulus cell; dose time effect relation; female; hormone action; in vitro study; nonhuman; protein expression; regulatory mechanism